2020
DOI: 10.4236/wjcd.2020.102011
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Epicardial Adipose Tissue Thickness Assessed by Multidetector Computed Tomography and Significance of Coronary Artery Disease

Abstract: Objective: To evaluate the relation between epicardial adipose tissue (EAT) thickness and also pericoronary fat assessed by Multidetector Computed Tomography (MDCT) with both calcium score and significance of coronary artery disease. Background: Epicardial adipose tissue (the visceral fat of the heart present under the visceral layer of the pericardium) has the same origin of abdominal visceral fat, which is known to be strongly related to the development of coronary artery atherosclerosis. Multidetector CT (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In a study conducted by Gać et al [13], it was indicated that positive correlation was noted between significant CAD, EAT thickness and PCFT in 80 suspected patients by coronary CT angiography. Other studies had similar results as our data regarding correlation of EAT thickness and PCFT and obstructive CAD [14,15]. However, You et al [16] reported that there was no correlation between PCFT and CAD severity.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted by Gać et al [13], it was indicated that positive correlation was noted between significant CAD, EAT thickness and PCFT in 80 suspected patients by coronary CT angiography. Other studies had similar results as our data regarding correlation of EAT thickness and PCFT and obstructive CAD [14,15]. However, You et al [16] reported that there was no correlation between PCFT and CAD severity.…”
Section: Discussionsupporting
confidence: 89%
“…They found a substantial correlation between EATT, calcium score and the Significance of coronary artery disease, with greater values in group III than in groups I and II. 18 , 7 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Demircelik et al, 7 who discovered that PCFT cut-off value ≥ 13.8 mm and EAT ≥6.8mm predict CAD obstruction. In addition, Samy et al 18 reported that the predicted EAT and PCFT values for obstructive CAD were ≥7.2 and 12.6 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CAD is major source of worldwide mortality and morbidity 6 .CAD is multifactor condition 6 .Visceral obesity is an independent risk factor for CAD 6 . EAT is a visceral fat that has been found to be associated with coronary artery plaques and calcification 6 . Irrespective of cardiovascular risk factors EAT leads to lethal and non-lethal coronary artery events in population 7 .…”
Section: Introductionmentioning
confidence: 99%